PENGARUH MODEL LEARNING CYCLE 5E TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMPN 11 PADANG - Rita Amwazir (Jurnal Edukasi dan Penelitian Matematika, 2019)
Mathematical communication is a basic ability that every students should have in learning. But the reality students’ mathematical communication in class VIII SMP N 11 Padang were still low, so that it needed to be improved. The teachers inclined use teacher centered learning. To solve this problem, teacher needed to apply a learning method that could facilitate the students in understanding the material and to build their knowledge. Learning method that appropriated was learning cycle 5E. Type of this research was quasi-experiment with Static Group Design. Based on data analysis that using the t-test, it is obtained P-value = 0.012< α = 0.05, it can conclude that students’ mathematical communication ability by using Learning Cycle 5E is better than the students that learn by using conventional learning.Keywords - conventional learning, learning cycle 5e, mathematical communication